Ability of Ethanol Extract from Ajwa and Sukkari Dates (Phoenix dactylifera L.) in Inhibiting the Growth of Methicillin-Resistant Staphylococcus aureus (MRSA) - Utami, Putra Rahmadea; Indrayati, Sri; Hayatang, Nur (Universitas Nahdlatul Ulama Surabaya, 2021)
Staphylococcus aureus is a pathogenic bacterium that spread throughout the world and still a problem that continues to increase both in hospitals and the community. Infections due to S. aureus usually treated with antibiotics, but in some cases, several strains of S. aureus found to be resistant to antibiotics, such as Methicillin-Resistant Staphylococcus aureus (MRSA). Based on the previous research, the ethanol extract from Ajwa and Sukkari dates formed an inhibitory zone against the MRSA bacteria growth. This study aims to determine the inhibition of the ethanol extract from Ajwa and Sukkari variety of dates (Phoenix dactylifera L.) on the S. aureus growth. The ethanol extract from Ajwa and Sukkari dates with a concentration of 5 mg/mL, 10 mg/mL, 15 mg/mL, and 20 mg/mL resulted in the same inhibition zone with a diameter of ≤ 6 mm which categorized as weak (resistant), whereas the positive control ciprofloxacin had a resistance zone with a diameter of 9 mm. This study results concluded that the ethanol extract of Ajwa and Sukkari dates only has a maximum concentration of 20 mg/mL, which is still classified as a low concentration and has not been able to inhibit MRSA bacteria growth.